A possibilidade de abordagem ético-moral no raciocínio jurídico : o aborto na visão de Dworkin e Finnis - Moreira, Alexandre Mussoi (2016)
The present work aims to determine the possibility of an ethical-moral approach to the juridical thought, by taking the abortion act in the views of Dworkin and Finnis as its analysis object. This assessment evidences the impossibility of any elaboration of the juridical reasoning in a way free from the moral-ethical questions, for the simple application of the positive juridical norms. In a current context of tension between the juridical-legal questions and those typically ethical-moral questions, which is not a novelty in the history of humanity, the regulation of this relation according to the criterion of the common good is the materialization itself of the justice in law. The ethical life is, in its intersubjective ambit, fair life (life in justice), which is sought by the law. The demands of the contemporary citizens regarding their rights, especially when concerns their individual choices (to be entitled to decide to have children, and when to have them; the right on his own body, et al), have been maintaining heated discussions which wrap up moral and ethical concepts. This study answers to the need of an ethical-moral approach of the juridical reasoning, placing the natural law as option of overcoming of the legal positivism. By using the comparative dialectical method, it has been made an option of assessing the thoughts of Ronald Dworkin and John Finnis, since both of them represent a change of a hermeneutic matrix which surpasses the separation between right and moral, from which the lawfulness refers to the moral-ethical correction of the action practiced by someone (in the specific case examined in this work, the abortion). With a jusnaturalist position, Finnis completely preclude the lawfulness of the act of abortion, whilst Dworkin admits exceptions to that, in what he is closer to the dominant position of the present civilization, which, regrettably, has been engaged in erasing any conception on the unconditional respect to life.